Information-seeking behavior of college students on religious tolerance through social media - Haekal Fajri Amrullah,; Mohd Nor Shahizan Ali,; Mohd Fauzi Sukimi, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Information seeking behavior is all information related activity. This activity occurs when there is a need for information to increase knowledge. The existence of social media provides a way for people to find information quickly. The openness of social media is why many people use it. Students have become one of the biggest group of people on social media. Besides studying, students in Indonesia have an important role in the social circumstance, one of which is regarding the religious tolerance. Students may serve as facilitators of religious harmony in Indonesia. However, they must firstly have enough knowledge to find information on religious tolerance, and thus social media can be a major source of information. The objectives of this research are to discover the levels of Indonesian university student’s information seeking behavior on religious tolerance through social media, knowing the obstacles in seeking the information and knowing the students’ responses after receiving the information through social media. This research employs a combination model of Behavioral models of seeking strategies, developed by David Ellis and T.D Wilson and a qualitative method by conducting a focus group discussion to six group of students in Jakarta, Indonesia from the various religion, namely Islam, Catholic, Protestantism, Hindu, Buddhist, and Confucianisme. Universities participated in this study are Universiti Mercu Buana Jakarta, Universiti Bina Nusantara, Universiti Negeri Jakarta dan Sekolah Tinggi Akuntansi Negara. Based on the two models employed, this study found that in general all the informants use social media in order to find an information and basically already have their own reference in searching for information regarding their religion. Furthermore, every individual has a different behavior when they are looking for an information. The main obstacles when seeking the information is hoax about the religious tolerance and the weak internet connection.